2012
DOI: 10.1111/j.1756-185x.2012.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adverse effect of anti‐tumor necrosis factor‐α biologics in treatment of rheumatoid arthritis: 5 years follow‐up

Abstract: Our results indicate that the use of TNFi therapy appeared to be as safe as traditional DMARDs in treatment of rheumatoid arthritis patients and long-term follow-up with careful examination is essential to pick up any abnormal ADEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Our findings are consistent with several published studies examining risks associated with different anti‐TNFs . One study that combined data from 4 major US databases reported that among patients with RA and other inflammatory diseases, the HZ risk was similar among different anti‐TNFs .…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with several published studies examining risks associated with different anti‐TNFs . One study that combined data from 4 major US databases reported that among patients with RA and other inflammatory diseases, the HZ risk was similar among different anti‐TNFs .…”
Section: Introductionsupporting
confidence: 92%
“…One study that combined data from 4 major US databases reported that among patients with RA and other inflammatory diseases, the HZ risk was similar among different anti‐TNFs . Similarly, using a cohort with 5 years of followup, another study showed that infliximab, adalimumab, and etanercept had comparable HZ risks and did not significantly increase HZ risk in comparison with nonbiologic disease‐modifying antirheumatic drugs (DMARDs) . In contrast, data from the German biologics register RABBIT suggested that adalimumab and infliximab may be associated with increased risk of HZ infection compared to etanercept .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some reports have described LD in patients receiving TNF-α inhibitors [22][23][24] and the relative risk for LD in patients treated with TNF-α inhibitor was between 16.5 and 21 compared to that for the overall population [22]. Although our patients received methotrexate and some reports described that the incidence of serious infections in patients with TNF-alpha inhibitor was not significantly higher than those with disease modifying anti-rheumatic drugs (DMARDs) [35,36], two in vivo studies have reinforced the notion of an increasing risk for LD among patients receiving TNF-α inhibitors. First, the administration of a TNF-α-neutralizing antibody to mice in vivo inhibited TNF-α activity and resulted in enhanced L. pneumophila growth in the mouse lung [37].…”
Section: Discussionmentioning
confidence: 84%
“…Because there are no adequately powered head‐to‐head randomized clinical trials with hospitalized infection as the outcome, results of studies using registries and administrative databases to evaluate the risk of hospitalized infection among RA patients treated with various biologic medications are inconsistent . For example, one study using the Dutch Rheumatoid Arthritis Monitoring registry showed that the risk of serious infection in RA patients treated with etanercept was lower than that in patients treated with adalimumab or infliximab .…”
Section: Discussionmentioning
confidence: 99%